Effect of accelerated ageing on seed quality parameters in onion - NIRAV MAKANI; N. SASIDHARAN; KALYAN RAO; ANKITRAVAL (Seed Research, 2026)
A laboratory experiment was carried out to study the effect of accelerated ageing on seed quality parameters in onion with completely randomized design (factorial). Seeds of ten onion genotypes were subjected to accelerated ageing at higher temperature and humidity (45°C and 100% RH) for various time intervals (0, 3, 5, and 7 days) and observation recorded. In this experiment parameters to be recorded was first count of germination, germination percentage, speed of germination, shoot, root and seedling length, seedling dry weight, vigour index-I and II, electrical conductivity of seed and enzyme activity of catalase, peroxidise and superoxide dismutase. Among all this characters the decreasing trend was found as ageing duration was increased except electrical conductivity, which was increasing with advanced ageing period. Among the ten onion genotypes, N-2-4-1 proved to be a promising cultivar, which retained seed vigour, viability and high enzymatic activity under prolonged artificial ageing conditions and could be stored for longer time and which can be employed for further breeding programmes.